Prevalence and correlates of burn-out among Nigerian medical doctors during the COVID-19 pandemic: a cross-sectional study - Ruth Eshikotse Pius; Janet Ngozi Ajuluchukwu; Alero Ann Roberts (BMJ Open)
Introduction Physician burn-out was an issue before the pandemic. Medical personnel have faced several clinical and non-clinical challenges because of the novel coronavirus (SARS-CoV-2) pandemic, which predisposes them to burn-out. There is a paucity of studies that shed light on the level of burn-out and its association with work-related factors for Nigerian medical doctors. This study aims to examine the level of burn-out among Nigerian medical doctors during the COVID-19 pandemic and explore possible associations between burn-out and sociodemographic, work-related and COVID-19-related factors.Methodology A cross-sectional study was conducted among 251 medical doctors in a tertiary hospital in Nigeria. A questionnaire was used to obtain sociodemographic history, work-associated factors, COVID-19-related parameters and burn-out history. Personal, work-related and patient-related burn-out were evaluated with the use of the Copenhagen Burnout Inventory.Results The number of doctors enrolled in this study was 251 with a median age of 34; 51.4% were males. The percentage of doctors who had personal, work-related and patient-related burn-out were 62.2%, 52.2 % and 27.5%, respectively. The univariate analysis revealed a correlation between burn-out scores and cadre, age, sex, years of experience, marital status, weekly work hours and number of calls. After multiple regression, female gender (p=0.012), those with less than 6 years of work experience (p=0.004) and those working for at least 71 hours in a week (p=0.0001) remained correlated with higher burn-out scores. Additionally, physicians who had a person with COVID-19 in their immediate environment had an independent correlation with higher work-related burn-out scores (p=0.043).Conclusion The prevalence of burn-out is high among Nigerian doctors and is linked to some sociodemographic, work-related and COVID-19-related factors. Due to the adverse effects of burn-out on physician well-being and patient care, strategies need to be put in place to identify and mitigate burn-out among Nigerian physicians.